Absence of Lateral Navigational Bias in Young Children. Issue 1 (August 2014) - Dye, Rosaline A.; Crawford, Thomas M.; McBeath, Michael K.
Previous research has shown American adults exhibit a systematic navigational bias to favor moving to the right when locomoting around obstacles and other people. To further investigate how and when the right-side navigational bias develops, the authors tested pre-school and early elementary school aged American children. Children ran down a straight pathway with an object at the center of the end-line. Unlike replicated findings with adults, both pre-school and early elementary school aged children showed no tendency to favor either side of the object. These findings support that the rightward navigation bias found in adults is not present in children up to elementary school, and suggest that the onset of bias occurs during the age range of late elementary or secondary school.